Syk Inhibitor Attenuates Polymicrobial Sepsis in FcgRIIb-Deficient Lupus Mouse Model, the Impact of Lupus Characteristics in Sepsis - Jiraphorn Issara-Amphorn; Wiwat Chancharoenthana; Peerapat Visitchanakun; Asada Leelahavanichkul (Karger Publishers, 2020)
The impact of spleen tyrosine kinase (Syk) signaling might be prominent in lupus because (i) Syk is a shared downstream signaling molecule among circulating immune complex, LPS, and (1→3)-β-D-glucan (BG), and (ii) all of these factors are detectable in the serum of Fc gamma receptor IIb-deficient (FcgRIIb−/−) mice with sepsis. As a proof of concept study, we activated macrophages with BG combined with LPS (BG + LPS). We found that BG + LPS predominantly upregulated Syk expression and proinflammatory cytokines in FcgRIIb−/− macrophages compared with wild-type (WT) macrophages. Syk inhibition downregulated several inflammatory pathways in FcgRIIb−/− macrophages activated with BG + LPS, as determined by RNA sequencing analysis, suggesting the potential anti-inflammatory impact of Syk inhibitors in lupus. Indeed, administration of a Syk inhibitor prior to cecal ligation and puncture (CLP) sepsis in FcgRIIb−/− mice reduced baseline lupus-induced proinflammatory cytokines and attenuated sepsis severity as evaluated by mortality, organ injury, serum LPS, and post-sepsis serum cytokines. In conclusion, it was easier to induce Syk expression in FcgRIIb−/− macrophages than in WT macrophages. This might be because of the loss of inhibitory signaling, which might be responsible for prominent Syk abundance in the spleens of 40-week-old FcgRIIb−/− mice and the potent effect of Syk inhibitor in lupus mice compared with WT.